2012
DOI: 10.1007/s11746-012-2185-9
|View full text |Cite
|
Sign up to set email alerts
|

Lipase‐Catalyzed Synthesis of Medium‐Long‐Medium Type Structured Lipids Using Tricaprylin and Trilinolenin as Substrate Models

Abstract: The synthesis of medium‐long‐medium type structured lipids (SL) by the interesterification of tricaprylin (TC) and trilinolenin (TLN), using selected commercial lipases from Rhizomucor miehei (Lipozyme RM IM) and Candida antarctica (Novozym 435) was investigated. Although the bioconversion yield (BY) for Lipozyme RM IM (24.7 %) was close to that for Novozym 435 (24.0 %), the initial enzyme activity was 6.3 μmol CLnC/g enzyme/min and 1.6 μmol CLnC/g enzyme/min, respectively. Lipozyme RM IM was subsequently sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Caprylic acid-linoleic acid-caprylic acid, and caprylic acid-oleic acid-caprylic acid were also produced at amount ratios of 4.09–4.19 and 8.44–8.53%, respectively. As an example of esterification type three, Bai et al ( 59 ) reported the utilization of tricaprylin and trilinolenin as substrates, and either Lipozyme RM IM or Novozyme 435 as a catalyst. Caprylic acid-linolenic acid-caprylic acid and caprylic acid-linolenic acid-linolenic acid were reported to be the dominant products.…”
Section: Methods Of Enzyme-catalyzed Mlm Lipid Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Caprylic acid-linoleic acid-caprylic acid, and caprylic acid-oleic acid-caprylic acid were also produced at amount ratios of 4.09–4.19 and 8.44–8.53%, respectively. As an example of esterification type three, Bai et al ( 59 ) reported the utilization of tricaprylin and trilinolenin as substrates, and either Lipozyme RM IM or Novozyme 435 as a catalyst. Caprylic acid-linolenic acid-caprylic acid and caprylic acid-linolenic acid-linolenic acid were reported to be the dominant products.…”
Section: Methods Of Enzyme-catalyzed Mlm Lipid Synthesismentioning
confidence: 99%
“…Moreover, palm kernel oil and coconut oil are reported as sources of MCFAs, containing higher amounts of lauric acid predominantly at sn -1,3 positions ( 40 ). Other potential substrates in MLM synthesis can be seen in Table 2 ( 39 , 43 , 56 - 59 ).…”
Section: Sources and Types Of Substrates For Mlm Lipid Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, the usage of two single TAG molecules and an sn-1,3-specific lipase might be a good choice to solve this problem. Bai et al (2013) adopted tricaprylin and trilinolenin as substrates and Lipozyme RM IM or Novozym 435 as a catalyst. CyLnCy and CyLnLn (Ln, linolenic acid) were found to be the most dominant TAGs.…”
Section: Production Of Structured Triacylglycerolsmentioning
confidence: 99%
“…The reason is because they are generally produced through lipase‐catalyzed interesterification of plant oils (usually soybean, rapeseed, and cottonseed oils) with MCTs (such as coconut and palm kernel oil). In similar manners to the industrial production of MLCTs, several recent studies have attempted to produce non‐MLM‐type MLCTs via interesterification of LCTs with MCTs using sn ‐1,3‐specific or nonspecific lipases as the biocatalyst (Bai and others ; Khodadadi and others ; Perignon and others ; Yang and others ; Khodadadi and Kermasha ,b). Non‐MLM‐type MLCTs were also obtained through acidolysis of LCTs with MCFAs (Casas‐Godoy and others ) or direct esterification of glycerol with a mixture of LCFAs and MCFAs in the presence of a nonspecific lipase (Yang and others ) or acidolysis of LCTs with a mixture of LCFAs and MCFAs using an sn ‐1,3‐specific lipase as the biocatalyst (Kocak and others ).…”
Section: Mlctsmentioning
confidence: 99%